DISCOURSE ON TABOOS IN ONLINE DATING: SEXUAL EXPRESSIONS OF JAKARTA OKCUPID USERS - Patresia P. Kirnandita; Mursyidatul Umamah; Maria Cherry Ndoen (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2019)
The popularity of global dating platforms has affected the dating behavior of urban daters, including those who live in Jakarta. Compared to match-seeking via print media decades ago, there are some changes in the way people present themselves and express their sexuality on dating platforms. On one of the dating platforms, OKCupid, some Jakarta users boldly stated their intention of looking for a hookup or non-heterosexual partner. This creates a problem in Indonesia, where most societies consider sexual acts and expressions such as premarital sex and non-heterosexual relationship as taboos. In this research, we examine the practice of OKCupid use by adult online daters in Jakarta, specifically about how they present themselves to express their diverse sexualities through OKCupid unique features. We argue that OKCupid features help its users to disclose themselves in a more specific manner, and thus facilitate them to find people with a shared interest and preferred gender or sexual orientation. Furthermore, in our informants' self-presentations, we found some strategies they utilized to preserve their privacy, avoid the consequences of normativity that is perpetuated from offline context, or target certain users as their potential matches. These strategies are dependent upon sociocultural dynamics as well as facilities developed by OKCupid.